Prevalence and factors associated with HIV infection among people with disabilities in Mali. (25th July 2022) - Cisse, Kadari; Ouedraogo, Henri Gautier; Compaore, Tegwinde Rebeca; Zida, Sylvie; Fomba, Harouna; Baldé, Boubacar; Ag Biga, Ahmed; Maïga, Seydou; Thera, Emmanuel; Sangaré, Mamadou; Kouanda, Seni
ABSTRACT: Previous studies on HIV and disability have reported the vulnerability of people with disabilities (PWDs) to HIV and the need to include them in HIV prevention programs. However, in Mali, data on HIV among this population is scarce. This study aims to estimate HIV prevalence and risk factors among people with disabilities in Mali. We conducted a household-based cross-sectional study in six regions of Mali. The Washington Group (WG) short questionnaire was used to identify PWDs in the household. A total of 1051 PWDs were included in the study. The prevalence of HIV infection among people with disabilities in Mali was 2.38% (25/1051), with a 95% confidence interval (CI) of 1.58%–3.44%. HIV prevalence was higher in women (3.31% [95%CI: 2.14–4.88]) than in men (0.78% [95%CI: 0.22–2.06]). People with visual or intellectual functional limitations were the most affected, with 3.93% (95%CI: 2.22–6.44) and 2.67% (95%CI: 0.56–8.28), respectively. Multivariate analysis shows that age, sex, type of disability and sexual violence are the risk factors for HIV infection among people with disabilities in Mali. These results suggest that HIV strategies should include people with disabilities in order to achieve the target of ending the HIV/AIDS epidemic by 2030 in Mali.